'Should I Buy, Hoard, or Hide?'- Consumers' responses to perceived scarcity. Issue 2 (15th March 2019) - Gupta, Shipra; Gentry, James W.
ABSTRACT: Scarce shopping situations often seem to have a greater value for consumers and trigger extreme behaviors. This study examines the effects of scarcity that is strategically created by the marketer in influencing consumer behavior. Drawing from reactance theory, it is suggested that, when scarcity is perceived to be strategically created by the retailer, consumers tend to exhibit deviant and competitive behaviors. The mediating role of emotions like anticipated regret is also examined. Further, the role of human traits like competitiveness and hedonic motivations in moderating the relationships between perceived scarcity and behaviors is also examined. The results of the study suggest that, under the conditions of perceived scarcity, consumers tend to exhibit behaviors like in-store hoarding, and in-store hiding, due in part to the increased urgency to buy. Also, the findings suggest a pertinent role of emotions and human traits in influencing the decision making under the condition of strategically-created scarcity.